2008
DOI: 10.1016/j.febslet.2008.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Physical and functional interactions between hnRNP K and PRMT family proteins

Abstract: Edited by Ivan SadowskiKeywords: hnRNP K PRMT HCV Core protein Protein-protein interaction a b s t r a c tThe mechanism underlying the protein-protein interaction of hnRNP K and PRMT family proteins is unclear. We examined and confirmed the arginine methylation of hnRNP K protein by PRMT1, not CARM1, via their direct binding. We also studied hnRNP K protein complexes containing CARM1, as well as PRMT1, using co-immunoprecipitation analysis. PRMT family proteins might be involved in the regulation of hnRNP K fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…Our results suggest that hnRNP A2 functions as a transcriptional coactivator by associating with enhanceosomes through protein-protein interactions with its N-terminal RNA binding domains. In support of our model, a recent study showed that another member of the hnRNP protein family, hnRNP K, also functions as a transcriptional activator (Moumen et al, 2005;Chan et al, 2009;Yuan et al, 2009). However, hnRNP A2 functions in a distinctly different manner than hnRNP K, which has DNA binding properties (Tomonaga and Levens, 1995).…”
Section: Discussionsupporting
confidence: 81%
“…Our results suggest that hnRNP A2 functions as a transcriptional coactivator by associating with enhanceosomes through protein-protein interactions with its N-terminal RNA binding domains. In support of our model, a recent study showed that another member of the hnRNP protein family, hnRNP K, also functions as a transcriptional activator (Moumen et al, 2005;Chan et al, 2009;Yuan et al, 2009). However, hnRNP A2 functions in a distinctly different manner than hnRNP K, which has DNA binding properties (Tomonaga and Levens, 1995).…”
Section: Discussionsupporting
confidence: 81%
“…Immunoprecipitation and in vivo reporter assays suggest a modulating function of hnRNP K methylation on p53 co-activator activity (Chen et al, 2008;Chan et al, 2009 (Gross et al, 2012). The interaction domains of both proteins bear asymmetrically dimethylated arginines.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3B, the hnRNP K-specific as well as the ADMA-specific antibody clearly precipitated hnRNP K from the E. coli extract confirming the reactivity of the ADMA-specific antibody with hnRNP K in the absence of other eukaryotic proteins. Furthermore, we excluded binding to PRMT1 which is complexed to hnRNP K [29], [40] (data not shown). We also observed binding of a small fraction of hnRNP K by the NMA-antibody.…”
Section: Resultsmentioning
confidence: 99%